FEATURES OF THE DEVELOPMENT OF SEGMENTS OF THE EUROPEAN LOGISTICS MARKET - STEBLIUK, Nataliia; GRYNKO, Tatyana; ROMANOV, Roman; POLOSIN, Anatoly (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines in detail the features of the development of segments of the European logistics market and emphasizes the multidimensional factors that determine its current state and prospects. It is established that the European logistics market has undergone a deep and dynamic transformation over the last century, shaped by the complex interaction of technological innovations, regulatory reforms, economic integration processes, and the rapid evolution of consumer needs. Logistics today is not only a supporting sector but also a vital component of the economic structure of the continent, ensuring the functioning of supply chains and strengthening Europe’s competitiveness in global markets. The study highlights the importance of the European logistics sector in maintaining the resilience of international trade and production networks, especially under the influence of global crises and geopolitical shifts. Particular attention is paid to the strategic priorities of development of the European transport industry until 2030, including digitalization, the introduction of smart transport systems, the transition to sustainable mobility, and the achievement of environmental goals in line with the Green Deal. Methodologically, the article applies the apparatus of fuzzy set theory to quantitatively evaluate the effectiveness of various projects and scenarios aimed at restoring and modernizing the European transport sector. This approach makes it possible to take into account uncertainty and variability of external conditions, ensuring a more reliable forecast. The prospects for improving the efficiency of measures to develop transport infrastructure, optimize logistics processes, and expand innovative services are analyzed. Based on the obtained results, a forecast of the growth rates of different segments of the European logistics services market has been developed, which can serve as a guideline for policymakers, investors, and market participants in forming long-term strategies.